Functional annotation of the T‐cell immunoglobulin mucin family in birds. Issue 3 (July 2016) - Hu, Tuanjun; Wu, Zhiguang; Vervelde, Lonneke; Rothwell, Lisa; Hume, David A.; Kaiser, Pete
Summary: T‐cell immunoglobulin and mucin (TIM) family molecules are cell membrane proteins, preferentially expressed on various immune cells and implicated in recognition and clearance of apoptotic cells. Little is known of their function outside human and mouse, and nothing outside mammals. We identified only two TIM genes ( chTIM ) in the chicken genome, putative orthologues of mammalian TIM1 and TIM4, and cloned the respective cDNAs. Like mammalian TIM1, chTIM1 expression was restricted to lymphoid tissues and immune cells. The gene chTIM4 encodes at least five splice variants with distinct expression profiles that also varied between strains of chicken. Expression of chTIM4 was detected in myeloid antigen‐presenting cells, and in γδ T cells, whereas mammalian TIM4 is not expressed in T cells. Like the mammalian proteins, chTIM1 and chTIM4 fusion proteins bind to phosphatidylserine, and are thereby implicated in recognition of apoptotic cells. The chTIM4–immunoglobulin fusion protein also had co‐stimulatory activity on chicken T cells, suggesting a function in antigen presentation.